Microfluidics as tool to prepare size-tunable PLGA nanoparticles with high curcumin encapsulation for efficient mucus penetration - Lababidi, Nashrawan; Sigal, Valentin; Koenneke, Aljoscha; Schwarzkopf, Konrad; Manz, Andreas; Schneider, Marc (Beilstein Journal of Nanotechnology, 2019)
Great challenges still remain to develop drug carriers able to penetrate biological barriers (such as the dense mucus in cystic fibrosis) and for the treatment of bacteria residing in biofilms, embedded in mucus. Drug carrier systems such as nanoparticles (NPs) require proper surface chemistry and small size to ensure their permeability through the hydrogel-like systems. We have employed a microfluidic system to fabricate poly(lactic-co-glycolic acid) (PLGA) nanoparticles coated with a muco-penetrating stabilizer (Pluronic), with a tunable hydrodynamic diameter ranging from 40 nm to 160 nm. The size dependence was evaluated by varying different parameters during preparation, namely polymer concentration, stabilizer concentration, solvent nature, the width of the focus mixing channel, flow rate ratio and total flow rate. Furthermore, the influence of the length of the focus mixing channel on the size was evaluated in order to better understand the nucleation–growth mechanism. Surprisingly, the channel length was revealed to have no effect on particle size for the chosen settings. In addition, curcumin was loaded (EE% of ≈68%) very efficiently into the nanoparticles. Finally, the permeability of muco-penetrating PLGA NPs through pulmonary human mucus was assessed; small NPs with a diameter of less than 100 nm showed fast permeation, underlining the potential of microfluidics for such pharmaceutical applications.
Keywords: curcumin; human pulmonary mucus; microfluidics; muco-penetrating nanoparticles; nanomedicine; permeability; PLGA nanoparticles